Wanprestasi pada Kredit Perbankan Akibat Pandemi Coronavirus Disease 2019 - Olga Nadina (Fakultas Hukum Universitas Airlangga, 2021)
This research discusses the concept of default on bank credit due to the Coronavirus Disease 2019 (Covid-19) pandemic. In order to maintain the national economic growth which is decreasing due to the Covid-19 pandemic, POJK No. 11/2020 juncto POJK No. 48/2020 regulates the provision of stimulus policies for bank debtors who experience difficulties in fulfilling their obligations to banks. After the enactment of this policy, the debtor is declared to be in default if there is an arrear that exceeds 90 days because the debtor does not meet the requirements for the accuracy of principal and/or interest payments in Article 3 paragraph (1) POJK No. 11/2020 juncto POJK No. 48/2020, so that debtor credit cannot be restructured. Due to the unsuccessful restructuring, based on Article 5 paragraph (1) POJK No. 11/2020 juncto POJK No. 48/2020, the credit quality remains in the non-performing loan category. The legal measures that can be taken by banks are through the efforts to save credit by credit restructuring. This study taken an example of a restructuring scheme at BRI Bank, by using the method of lowering interest rates, changes in principal installment scheduling and extension of the credit period. If the loan restructuring is not successful, then the bank needs to handle it by credit settlement efforts.Keywords: Default; Bank Credits; Covid-19.Penelitian ini membahas mengenai wanprestasi pada kredit perbankan akibat pandemi Coronavirus Disease 2019 (Covid-19). Untuk menjaga pertumbuhan perekonomian nasional yang sedang menurun akibat pandemi Covid-19, diterbitkan POJK No. 11/2020 juncto POJK No. 48/2020 yang mengatur mengenai pemberian kebijakan stimulus bagi debitur bank yang mengalami kesulitan untuk memenuhi kewajibannya kepada bank. Pasca berlakunya kebijakan tersebut, debitur dinyatakan melakukan wanprestasi apabila, terjadi tunggakan yang melebihi 90 hari dikarenakan debitur tersebut tidak memenuhi persyaratan ketepatan pembayaran pokok dan/atau bunga dalam Pasal 3 ayat (1) POJK No. 11/2020 juncto POJK No. 48/2020, sehingga kredit debitur tidak dapat dilakukan restrukturisasi. Oleh karena tidak berhasil direstrukturisasi, berdasarkan Pasal 5 ayat (1) POJK No. 11/2020 juncto POJK No. 48/2020 maka kualitas kredit tetap dalam kategori kredit bermasalah. Upaya penanganan yang dapat dilakukan bank yaitu melalui upaya penyelamatan kredit dengan melakukan restrukturisasi kredit. Penelitian ini mengambil contoh skema restrukturisasi pada Bank BRI, yaitu dengan menggunakan metode penurunan suku bunga, perubahan penjadwalan angsuran pokok dan perpanjangan jangka waktu kredit. Jika restrukturisasi kredit tidak berhasil, maka dilakukan upaya penanganan melalui upaya penyelesaian kredit.Kata Kunci: Wanprestasi; Kredit Perbankan; Covid-19.